Identification of a novel ANK1 mutation in hereditary spherocytosis co‐existing with BWS. Issue 4 (25th February 2022) - Zhang, Qinghua; Zhang, Chuan; Wang, Yupei; Hao, Shengjv; Shi, Jingyun; Feng, Xuan; Zheng, Lei; Wang, Xin; Xue, Chen; Zhou, Bingbo; Liu, Furong; Zhao, Fangping; et al.
Abstract: Background: Beckwith–Wiedemann syndrome (BWS) is an inherited disorder affecting 1 in 10, 500 to 13, 700 newborns worldwide. The disease is caused in a vast majority of patients by a molecular defect in the imprinted chromosome 11p15.5. Hereditary spherocytosis (HS) is a form of hemolytic anemia associated with a variety of mutations leading to congenital red blood cell (RBC) membrane defects. The prevalence of HS varies by geographic regions around the world, ranging from 1.2 in 100, 000 in Asia to 1 in 2000 in Northern Europe. Methods and Results: Herein, we report for the first time a rare case diagnosed with co‐existing BWS and HS. Based on the classical presentations, including macroglossia, hepatosplenomegaly, and macrosomia, the patient was first suspected with BWS. MS‐MLPA confirmed the BWS diagnosis based on hypomethylation of maternal 11p15.5 ( KCNQ1OT1 ), but no copy number variations in chromosome 11 was detected by CNV‐seq. Nevertheless, to scrutinize molecular causes of other symptoms of the patient, including anemia, hyperbilirubinemia, and jaundice, a whole exome sequencing (WES) was performed. We identified a novel and de novo mutation in ANK1 gene (c.520delC). This frameshift mutation of ANK1 gene results in a truncated protein without important functional domains and impaired membrane stability and structure of the resultant red blood cells (RBCs), leading to a definitive diagnosis of HS. Conclusion: The present case demonstrated that multiple genetic and epigenetic aberrations might co‐exist in the complex genetic diseases. For such kind of complicated cases, the different types of molecular tests, such as WES and MS‐MLPA, should be utilized in combination to reveal independent causal molecular events. The identifications from this study added new insights into the understanding of molecular mechanisms underlying the co‐existing HS and BWS. Abstract : We report a rare case with a novel mutation in ANK1 gene and concomitant BWS and HS diagnosed.